Your Second First Impression: The Art of Startup Rebranding - Procházka, David Anthony; Balášová, Daniela; Bočková, Kateřina (Journal of Posthumanism, 2025)
Presented paper explores the rebranding strategy of the startup GREEZIIS and its impact on marketing performance and brand perception. It examines how strategic marketing, effective communication, and proper audience targeting can support brand success. The study uses a case analysis method, evaluating data such as product sales, social media growth, and customer engagement before and after the rebranding. Qualitative insights were gathered through interviews with the founder and investors. Findings suggest positive development, though a longer timeframe is needed for full evaluation.